Highly efficient magnetic hyperthermia ablation of tumors using injectable polymethylmethacrylate–Fe3O4. Issue 5 (12th January 2017) - Ling, Yi; Tang, Xiuzhen; Wang, Fengjuan; Zhou, Xiaohan; Wang, Ronghui; Deng, Liming; Shang, Tingting; Liang, Bing; Li, Pan; Ran, Haitao; Wang, Zhigang; Hu, Bing; et al.
Abstract : Magnetic hyperthermia is a promising minimally invasive technique for tumor therapy which has drawn much attention. Abstract : Magnetic hyperthermia is a promising minimally invasive technique for tumor therapy which has drawn much attention. However, the currently used magnetic materials have their limitations. In this study, we developed an injectable, liquid to solid phase transitional magnetic material, polymethylmethacrylate (PMMA)–Fe3 O4 designed for highly efficient magnetic hyperthermia ablation of tumors. The PMMA–Fe3 O4 was prepared by the incorporation of PMMA and the Fe3 O4 . The morphology characterization, the magnetic properties and the heating efficiency of PMMA–Fe3 O4 were studied. The Fe3 O4 particles were evenly distributed in the PMMA and the hysteresis curve of Fe3 O4 and PMMA–Fe3 O4 indicated that they were magnetic materials. When exposed to an alternating current magnetic field in vitro, the magnetic PMMA–Fe3 O4 generated heat. The increased temperature of excised bovine liver was positively correlated to the iron content and time, which suggested that the temperature inside the tumor was controllable. The ablated liver tissue area for 0.1 ml 10% PMMA–Fe3 O4 was 1.24 ± 0.28, 1.70 ± 0.57, 2.76 ± 0.31, 4.17 ± 1.07 cm 3, respectively, at 60, 120, 180 and 240 s time points. In the in vivo animal experiments, a MB-231 breast cancer xenograft model was obtained in nude mice. In this tumor model, PMMA–Fe3 O4 was injected precisely using guided ultrasound imaging. After the injection, the computer tomography images showed that it was well confined in the tumor tissues without any leakage. The tumors were completely ablated by a dose of 0.1 ml, 10% PMMA–Fe3 O4 with 180 s exposure time in the magnetic field. Our results demonstrated that PMMA–Fe3 O4 was an excellent magnetic material for the localized magnetic hyperthermia ablation of tumors.